‘Then Israel Bowed Himself…’ (Genesis 47.31) - de Hoop, Raymond (Journal for the study of the Old Testament, 2004)
In Gen. 47.31b we find the phrase [ILLEGIBLE], which is generally interpreted as ‘then Israel bowed himself at the head of the bed’. Yet this interpretation does not make much sense in the context and commentators are puzzled about its meaning. This article surveys the possible meaning of the phrase with the help of the LXX and Peshitta, traditions which interpret the final word [ILLEGIBLE] as ‘staff’. The rendering of the Versions suggests a possible meaning of ‘staff, tribe’ for the Hebrew term, leading to the more common interpretation of [ILLEGIBLE] [ILLEGIBLE] as ‘head of the tribe’. The suggested interpretation implies that the dying patriarch bowed down for the new pater familias, Joseph. Finally some considerations are given regarding the historical context in which Joseph appears as the new pater familias, the successor of his father, the patriarch Israel.